Comparative study of toxicity for thermoplastic polyurethane and its flame-retardant composites. (October 2019) - Liu, Chen; Zong, Ruowen; Chen, Haiyan; Wang, Junling; Wu, Chaopeng
Toxic product in fire disasters is the most important reason for fire casualties. With wide application of polymer material, the toxic products in fire effluents are getting more and more diversified and complicated. Polyurethane is one of the most widely used materials. In this article, the fire toxicant release has been evaluated for thermoplastic polyurethane (TPU) and its flame-retardant composites. Ammonium polyphosphate (APP), aluminum hydroxide (ATH), and nano-montmorillonite (MMT) were combined into different flame-retardant combinations at certain ratios. Three kinds of flame-retardant combinations (APP-ATH, APP-MMT, and APP-ATH-MMT) were blended to reduce toxicity of TPU. The properties of thermal stability and decomposition were characterized by thermogravimetric analysis (TGA). TGA/infrared spectrometry, static tube furnace, and steady-state tube furnace were used to evaluate the toxic gases, including CO and HCN. Fractional effective dose (FED) was calculated based on the concentrations of CO, CO2, and HCN. The results showed that more than 50% toxicity effect in FED was accounted for HCN. The comprehensive toxicity of TPU was reduced in the samples with APP-ATH and APP-ATH-MMT. The yields of CO, CO2, and O2 consumption were indicated much lower in the samples with APP-ATH-MMT than the other two combinations.